2015
DOI: 10.1002/mnfr.201400649
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of dietary capsaicin on liver fibrosis in mice

Abstract: Dietary CPS has potential benefits in the therapy of cholestatic liver fibrosis and in the prophylaxis of hepatotoxic-induced liver injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 32 publications
2
9
0
Order By: Relevance
“…Our results showed that CPS administration dose-dependently inhibited serum hepatotoxicity and hepatic lipid peroxidation and increased the weights of body and liver in DMN-treated rats. These results are accordance with those in previously reported studies , and demonstrate the protective effect of CPS in the setting of chronic liver diseases.…”
Section: Discussionsupporting
confidence: 94%
“…Our results showed that CPS administration dose-dependently inhibited serum hepatotoxicity and hepatic lipid peroxidation and increased the weights of body and liver in DMN-treated rats. These results are accordance with those in previously reported studies , and demonstrate the protective effect of CPS in the setting of chronic liver diseases.…”
Section: Discussionsupporting
confidence: 94%
“…Bitencourt S et al, at EASL 50 th International Liver Congress, Vienna, stated the inhibitory effects of capsaicin as a dietary supplement on HSC activity in mice with arti icially induced liver ibrosis. Mice fed capsaicin prior to toxin exposure were protected against the development of liver injury and up-regulation of ibrosis activation markers (Bitencourt, 2015).…”
Section: Capsaicinmentioning
confidence: 99%
“…Some reports show that capsaicin alleviates CCl 4 -induced liver fibrosis in rats and mice, via enhancing peroxisome proliferator-activated receptor gamma (PPARγ) and nuclear factor-erythroid derived 2-related factor 2 (Nrf2)-associated antioxidation, suppressing tumor necrosis factor α (TNF-α) signaling or autophagy of HSCs activation [18][19][20][21][22]. Furthermore, capsaicin also significantly improves bile duct ligation (BDL)-induced mouse liver fibrosis, which may involve the reduction of F4/80 + (a marker of Kupffer cells) expression [19]. Moreover, capsaicin ameliorates dimethylnitrosamine (DMN)-induced rat liver fibrosis through the suppression of the TGF-β1/Smad pathway mediated by PPARγ activation [23].…”
Section: Capsaicinmentioning
confidence: 99%